In-situ Investigation of the Microstructure Evolution in Long-Period-Stacking-Ordered (LPSO) Magnesium Alloys as a Function of the Temperature - Máthis, Kristián; Drozdenko, Daria; Németh, Gergely; Harjo, Stefanus; Gong, Wu; Aizawa, Kazuya; Yamasaki, Michiaki; Kawamura, Yoshihito (Frontiers in Materials, 2019)
Deformation behavior of two Mg–Zn–Y magnesium alloys, having a different fraction of the long-period-stacking-ordered (LPSO) phase, has been investigated at room temperature and 200°C by a combination of in-situ neutron diffraction (ND) and acoustic emission (AE) measurements. The results indicate that the twinning in the magnesium matrix and the kinking in the LPSO phase strongly depend on the composition of the material and the testing temperature. Further, active deformation mechanisms and particularly the load transfer from the magnesium matrix to the LPSO phase define the mechanical properties of the investigated alloys.